2005
DOI: 10.1524/ract.2005.93.7.409
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of technetium(IV) chloride under gamma irradiation

Abstract: Technetium speciation / Gamma radiolysis / Technetium one-electron oxidation / Radioactive waste disposalSummary. Speciation of Tc in aqueous solution is a complex phenomenon because several parameters intervene simultaneously. We show under gamma radiations, it is completely modified. At pH 8.5 TcO 2 is oxidized to Tc(VII) with a yield of 1.38 × 10 −7 mol J −1 . At pH 1.5, it was demonstrated that Tc is present as hydroxylated species Tc n O y (4n−2y)+ (L. Vichot, M. Fattahi, M. Musikas: Radiochim. Acta 91, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…1 Previous studies investigated the effect of γ-radiolysis on the speciation of Tc in hydrochloric and sulfuric acids. 2,3 In dilute sulfuric acid, it was shown that Tc(IV) colloids were formed under irradiation by X-rays of pertechnetate solutions. 4,5 Under α-irradiation, the formation of colloidal species has never been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Previous studies investigated the effect of γ-radiolysis on the speciation of Tc in hydrochloric and sulfuric acids. 2,3 In dilute sulfuric acid, it was shown that Tc(IV) colloids were formed under irradiation by X-rays of pertechnetate solutions. 4,5 Under α-irradiation, the formation of colloidal species has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have been performed under γ-irradiation, the effect of α-irradiation on the behavior of Tc species in acidic media has been less studied . Previous studies investigated the effect of γ-radiolysis on the speciation of Tc in hydrochloric and sulfuric acids. , In dilute sulfuric acid, it was shown that Tc(IV) colloids were formed under irradiation by X-rays of pertechnetate solutions. , Under α-irradiation, the formation of colloidal species has never been reported. Even though α-radiolysis of dilute sulfuric acid solutions was studied, , no data have been reported at high concentration of H 2 SO 4 .…”
Section: Introductionmentioning
confidence: 99%